Single-phase full-bridge inverter control based on discrete adaptive sliding mode algorithm with error compensation - Zhang, Yun; Tang, Zhenyu; Xu, Fenghui; Zhou, Kaichen; Yang, Kun (PloS one, 2025)
This paper proposes that the control process of the single-phase full bridge inverter circuit is equivalent to two buck circuits, and the control strategy of the DC-DC circuit is adopted to enable the output voltage to track the given sine wave target value in real time, realizing the control of the inverter circuit, simplifying the control process, and enhancing the anti-interference ability of the system. On the basis of traditional discrete sliding mode control, a new adaptive approach rate is introduced, which can dynamically adjust the control gain according to the distance between the sliding surface and the sliding band. When the state variable is far from the sliding surface, it accelerates the approach speed, and when the state variable approaches the sliding surface, it reduces the approach speed, which can effectively reduce chattering. As a result, the width level of the sliding mode band is reduced from the traditional O ( T ) to the same level O ( T 3 ), and the width of the sliding mode band is significantly reduced, significantly improving the control accuracy and jitter suppression ability. The proposed control method was rigorously mathematically proven in terms of sliding mode bandwidth, jitter range, and convergence steps, and the advantages of the improved method in voltage tracking speed, steady-state error, and disturbance rejection performance were verified through multiple simulation experiments.